2017
DOI: 10.1111/liv.13595
|View full text |Cite
|
Sign up to set email alerts
|

Endoglin in human liver disease and murine models of liver fibrosis—A protective factor against liver fibrosis

Abstract: Background & AimsLiver fibrosis is the outcome of chronic liver injury. Transforming growth factor‐β (TGF‐β) is a major profibrogenic cytokine modulating hepatic stellate cell (HSC) activation and extracellular matrix homeostasis. This study analyses the effect of Endoglin (Eng), a TGF‐β type III auxiliary receptor, on fibrogenesis in two models of liver injury by HSC‐specific endoglin deletion.MethodsEng expression was measured in human and murine samples of liver injury. After generating GFAPCre(+)EngΔ HSC m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…Other studies, on the other hand, show that endoglin might also be protective during fibrosis. In a murine model for liver fibrosis, endoglin deficiency enhanced the expression of pro-fibrotic factors such as α-SMA and fibronectin [118]. The authors suggest that endoglin might work protectively by modulating ALK1-versus ALK5-dependent TGF-β signaling.…”
Section: Endoglin-expressing Fibroblasts In Fibrosismentioning
confidence: 98%
“…Other studies, on the other hand, show that endoglin might also be protective during fibrosis. In a murine model for liver fibrosis, endoglin deficiency enhanced the expression of pro-fibrotic factors such as α-SMA and fibronectin [118]. The authors suggest that endoglin might work protectively by modulating ALK1-versus ALK5-dependent TGF-β signaling.…”
Section: Endoglin-expressing Fibroblasts In Fibrosismentioning
confidence: 98%
“…Hepatic stellate cells (HSCs) are the main source of collagen and ECM [2]. After liver injury, resting HSCs are transformed into activated myofibroblasts, followed by ECM synthesis [3]. When the synthesis of ECM is greater than consumption, hepatic fibrosis develops gradually, leading to liver dysfunction, portal hypertension, and hepatocellular carcinoma (HCC) [1,4].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, endoglin is expressed in the liver with a much higher abundance of the L-ENG splice variant [13]. The research on the murine model has shown that S-ENG is an anti-angiogenic molecule, in contrast to the pro-angiogenic activity of L-endoglin [77].…”
Section: Endoglin—characteristics Of the Moleculementioning
confidence: 99%
“…The commonly suggested role of CD105 in carcinogenesis is based on clinical studies, as well as in vitro and animal model experiments. The results of said research indicate the potential role of CD105 in liver fibrosis [11,12,13] and hepatocellular carcinoma progression [12,14,15,16,17,18,19,20,21,22]. However, the observations concerning quantitative endoglin expression and its prognostic role in HCC are not coherent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation